Bi1Te1 is a dual topological insulator - Markus Eschbach (Nature Portfolio, 2017)
Coexistence of a topological insulator phase and a topological crystalline insulator phase helps to maintain topological properties under a controlled symmetry breaking perturbation. Here, Eschbacket al. report a superlattice of Bi and Bi2Te3to be such a dual topological insulator.